People in y-Walk teeshirts celebrating the YWCA's 75th anniversary - Unknown:::Creator::::::::::::
Photograph shows a group portrait of people celebrating 75 years of the YWCA in San Jose. The majority of them are wearing blue and pink y-Walk tee shirts. A couple of people standing next to a y-Walk balloon bouquet are wearing clothing that reflects an earlier era. There is a white banner that reads: "Celebrates 75 years 1914-1975" and a red y-Walk banner behind the group.